Propuesta de sinonimia para las especies de cangrejo dulceacuícolaHypolobocera solimani e Hypolobocera triangula de Colombia - R. Campos, Martha (2008)
It is proposed that Hypolobocera solimani and H. triangula be considered junior synonyms of H. alata and H. rotundilobata, respectively. We state that the following morphological differences represent natural variations within the population: a) first male gonopod, third maxilliped and larger cheliped between H. alata and H. solimani, and b) the differences of the first male gonopod between H. rotundilobata and H. triangula.